Deepening Democracy in Indonesia? : Direct Elections for Local Leaders (Pilkada) (Institute of Southeast Asian Studies, 2009)
The contributors take a generally positive view of the impact of local elections on the development of Indonesia's democracy. But they are not blind to the problems. The proliferation of political parties with similar ideological bases has meant that party affiliations are very tenuous. This, toogether with the fact that support at the local level was frequently sold to the highest bidder, led to all kinds of unlikely coalitions. Most authors nevertheless find reason for optimism. Wealth, they note, did not guarantee victory. Instead, the winners tended to be those who were popular or were rooted in their districts. Incumbents who won generally did so because they had performed well in office, while those who lost often had poor records. Indeed, one of the striking characteristics of these elections is the extent to which voters have looked to the personalities and leadership qualities of the candidates rather than the parties or coalitions they represented. Have local elections depeened Indonesia's democracy? The optimistic answer provided by this book is that on balance, they have